Culture Industry and Japanese Identity in Snack and Drinks Products in Indonesia - Diana Puspitasari; Yudi Suryadi; Heri Widodo (IZUMI, 2022)
This research discusses the Japanese identity inherent in food and beverage products produced and marketed in Indonesia with a cultural industry perspective. The purpose of this research is to reveal the form of Japanese identity attached to the products and its relationship with the cultural industry so that it will appear that the relationship between the two is interrelated and mutually supportive. This research is descriptive qualitative using the content analysis method on product packaging design on a cultural industry approach. The results found a Japanese identity in writings form, words, pictures, flavor variations, and a compilation of Japanese and local flavor variants on product packaging. The packaging design is made as if it is transferring Japan into the packaging of products. In the small packaging, it summarizes the discourse of the culture industry as well as provides a simulacrum for Japanese lovers. The use of Japanese identity has become a widespread cultural commodity in the financial and cultural economy. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor